Social Network Analysis on Odd-Even Policy in Bogor City - Imsar Gunawan; Manik Sunuantari; Yoedo Shambodo (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
Social network analysis (SNA) has been widely used in epidemiology to understand how the structure of the relationship is formed in the odd-even policy implemented in the city of Bogor. SNA can also be an appropiate tool for mapping the effectiveness of a policy. The public policy implemented by the Mayor of Bogor regarding odd-even policy in Bogor shaped various responses from the community. This study aims to determine the effectiveness of the Odd-Even policy through Twitter’s hashtagh #GanjilGenapBogor. The theory used was media convergence theory, with the concept of User Generated Content (UGC). The method used was network analysis with a qualitative approach. The results indicated that the users of Twitter’s social media showed various responses to this issue. The responses formed various conversations among the users. From these conversations, the Popularity Centrality of the actors involved was formed. Each actor plays a role in the formation of public opinion. Actors who are involed in these conversations, played an important role in creating interrelated group communication networks. The exchange of information carried out by the main actors in the communication network aims to see how much influence is generated to the followers or members of the network created by the main actor. This circumstance brings up one dominant actor, which is called ‘opinion leader’. In addition, this response resulted in the emergence of news sentiments. Sentiments that appear in the public tend to be negative. These sentiments touched 55% of the total coverage on various news media platforms.